2018
DOI: 10.1002/bies.201800027
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota‐Inflammasome Hypothesis of Major Depression

Abstract: We propose the "microbiota-inflammasome" hypothesis of major depressive disorder (MDD, a mental illness affecting the way a person feels and thinks, characterized by long-lasting feelings of sadness). We hypothesize that pathological shifts in gut microbiota composition (dysbiosis) caused by stress and gut conditions result in the upregulation of pro-inflammatory pathways mediated by the Nod-like receptors family pyrin domain containing 3 (NLRP3) inflammasome (an intracellular platform involved in the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
102
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 118 publications
(200 reference statements)
1
102
0
1
Order By: Relevance
“…Recent reports on the intestinal microbiota of human psychiatric disorders including depression and bipolar disorder report a similar pattern of reduced diversity. Other studies have also shown unaltered and also increased microbiome diversity in patients with depression as described in a recent paper introducing the microbiota‐inflammasome hypothesis . Based on results from seven studies on major depression, it was concluded that depression seems associated with altered microbiota composition .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent reports on the intestinal microbiota of human psychiatric disorders including depression and bipolar disorder report a similar pattern of reduced diversity. Other studies have also shown unaltered and also increased microbiome diversity in patients with depression as described in a recent paper introducing the microbiota‐inflammasome hypothesis . Based on results from seven studies on major depression, it was concluded that depression seems associated with altered microbiota composition .…”
Section: Introductionmentioning
confidence: 94%
“…Other studies have also shown unaltered and also increased microbiome diversity in patients with depression as described in a recent paper introducing the microbiota‐inflammasome hypothesis . Based on results from seven studies on major depression, it was concluded that depression seems associated with altered microbiota composition . The altered microbiota diversity in the referred psychiatric disorders may be related to intrinsic disease heritability per se as well as to adjunct lifestyle factors including diet, smoking, and alcohol consumption as well as medication use.…”
Section: Introductionmentioning
confidence: 94%
“…As a common mental disorder accompanied by high disability and suicide, major depressive disorder MDD has become a worldwide issue concerned [1]. In recent years, more and more evidences were reported to indicate that gut microbes might take part in the course of MDD [2][3][4]. In several paralleled researches, MDD patients showed speci c features of gut microbes differing from normal controls [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For example, it has been shown that the Bacteroides genus in patients with MDD was increased, while the Lachnospiraceae genus was decreased. 5,14,15 Further consideration on the mechanisms central to the role that gut microorganisms may have on the pathogenesis of MDD is of significant importance. Emerging evidence with the administration of probiotics has demonstrated a decrease in neuroinflammation, a pathogenic characteristic of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence with the administration of probiotics has demonstrated a decrease in neuroinflammation, a pathogenic characteristic of depression. 5,14,15 Further consideration on the mechanisms central to the role that gut microorganisms may have on the pathogenesis of MDD is of significant importance.…”
Section: Introductionmentioning
confidence: 99%